A GIS-Independent method of Stream-Order-Law Ratios Prediction in Catchments for direct Runoff Hydrograph Estimation - Mostafa Akbari Kheirabadi; Touraj Sabzevari; Andrea Petroselli; Mohsen Tarahi (Acta Scientiarum Polonorum. Formatio Circumiectus, 2024)
Aim of the study: There are two main aims of this paper: to present equations that can predict the stream-order-law ratios on the basis of length, slope of the stream, and area of the catchment; to apply the predicted stream-order-law ratios in estimating direct runoff of catchments by GIUH method.